A roadmap to surgery in osteogenesis imperfecta: results of an international collaboration of patient organizations and interdisciplinary care teams. (8th October 2021) - Sakkers, Ralph J; Montpetit, Kathleen; Tsimicalis, Argerie; Wirth, Thomas; Verhoef, Marjolein; Hamdy, Reginald; Ouellet, Jean A; Castelein, Rene M; Damas, Chantal; Janus, Guus J; Nijhuis, Wouter H; Panzeri, Leonardo; et al.
Abstract : Background and purpose — Involvement of patient organizations is steadily increasing in guidelines for treatment of various diseases and conditions for better care from the patient's viewpoint and better comparability of outcomes. For this reason, the Osteogenesis Imperfecta Federation Europe and the Care4BrittleBones Foundation convened an interdisciplinary task force of 3 members from patient organizations and 12 healthcare professionals from recognized centers for interdisciplinary care for children and adults with osteogenesis imperfecta (OI) to develop guidelines for a basic roadmap to surgery in OI. Methods — All information from 9 telephone conferences, expert consultations, and face-to-face meetings during the International Conference for Quality of Life for Osteogenesis Imperfecta 2019 was used by the task force to define themes and associated recommendations. Results — Consensus on recommendations was reached within 4 themes: the interdisciplinary approach, the surgical decision-making conversation, surgical technique guidelines for OI, and the feedback loop after surgery. Interpretation — The basic guidelines of this roadmap for the interdisciplinary approach to surgical care in children and adults with OI is expected to improve standardization of clinical practice and comparability of outcomes across treatment centers.